Shredlage Processing Affects the Digestibility of Maize Silage - Filip Jančík; Petra Kubelková; Radko Loučka; Václav Jambor; Dana Kumprechtová; Petr Homolka; Veronika Koukolová; Yvona Tyrolová; Alena Výborná (Agronomy, 2022)
Maize silage is one of the most important feeds for ruminant nutrition and various production methods can have a significant impact on their quality, especially the utilization of nutrients. The objective of the study was to evaluate the effect of conventional and shredlage processing of harvested maize on kernel processing, fermentation profile, physically effective fibre and digestibility of maize silage. A stay-green maize hybrid was harvested with a conventional forage harvester (CON; theoretical length of cut 10 mm; conventional rollers with a 30% difference in roller speed; the rollers have a horizontally teeth; 1-mm roll clearance) or a shredlage processor (SHR; theoretical length of cut 25 mm; Shredlage crop processor with 50% difference in roller speed; the rollers have sawtooth teeth with a counter-rotating spiral groove; 1-mm clearance) and stored in experimental silos. The experimental silages were analysed for chemical composition (dry matter, organic matter, crude protein, crude fibre, neutral detergent fibre, starch), fermentation parameters (pH, lactate, acetate, ammonia), processing quality (kernel processing score, particle size), physically effective neutral detergent fibre (peNDF) and in vivo nutrient digestibility. The shredlage processing (SHR) of maize plants did not have an effect on the silage fermentation profile. On the other hand, the SHR treatment significantly increased kernel processing score (p < 0.01) and peNDF content (p < 0.01). SHR also increased in vivo digestibility significantly, namely that of dry matter (DM), organic matter, starch, crude fibre and neutral detergent fibre (NDF). An increase in nutrient digestibility leads to higher values of NEL. The presented results show positive effects of shredlage processing on quality and digestibility of maize silage.